Changes in body composition and physical performance after a six-week international tour in young Chilean female tennis players - Luna-Villouta, P.; Contreras, L. V.; Salazar, C. M.; Valderrama, J. F.; Matus-Castillo, C.; Flores-Rivera, C.; Paredes-Arias, M.; Vargas-Vitoria, R. (Sports, 2024)
Junior tennis players travel a lot to play tennis tournaments; this causes them to spend a lot of time away from their homes and disrupts their training, which could reduce their performance and increase the risk of injury. The purpose of this study was to analyze the changes in physical performance and body composition after a six-week international tour in young Chilean female tennis players. Thirty young female tennis players (15.4 ± 0.6) participated in this study. Body weight, skinfolds, and perimeters were measured. Body fat percentage (BFP) and skeletal muscle mass (SMM) were calculated. For physical performance, 5 m sprint, the 505 with stationary start test (505 test), the pro-agility test, countermovement jump (CMJ), and medicine ball throw (MBT) were evaluated. The results show a significant increase in BFP and decrease in SMM (p < 0.01; d = -0.18 and 0.19, respectively). In terms of physical performance, 5 m sprint, the 505 test (p < 0.01; d = -0.95 and -0.95, respectively), CMJ, MBT, and HJ significantly decreased post-tour (p < 0.05; d = 0.96, 0.89 and 0.47, respectively). We conclude that, after a six-week international tour, there were changes in body composition and a significant decrease in 5 m sprint, the 505 test, CMJ, and MBT.